Lightweight high-stiffness single-phase foam metamaterials with fluted resonant cavities for low frequency bandgaps. (September 2021) - Cheng, Shuliang; Yao, Jinxin; Ding, Qian; Xin, Yajun; Sun, Yongtao; Gao, Haoqiang
Abstract: In this paper, a lightweight three-dimensional single phase phonon crystal structure with high stiffness is proposed. Its band gap is as low as 250 Hz, which has both bearing capacity and low frequency vibration and noise reduction ability. The band gap characteristics, vibration modes and transmission characteristics of the structure are analysed by finite element simulation. The results show that the structure can open a complete band gap when the normalized frequency is less than 0.02, and the coupling between the elastic wave propagation and the local resonances of the resonant element is the key to open the band gap. Geometric parameters can be used to control the band gap position, while material parameters do not affect the relative position and bandwidth of the band gap.